Causality Analysis Between Exchange Rate, Current Balance Sheet, Inflation, and Gross Domestic Product in ASEAN-5 1980-2022 - Ulpa, Fithri Atika (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This research investigates the causality between exchange rate, current balance sheet, inflation, and gross domestic product in ASEAN 5 from 1980 to 2022. The method employs the Granger causality test. This research finds weak evidence of a J-curve effect on the current account balance in Indonesia because empirical results with several tests and models reject the J-curve hypothesis and do not find evidence of an influence of the rupiah exchange rate on Indonesia's current account balance in the long term so that it can the conclusion is drawn that: (1) There is no causal relationship between the current account balance and the exchange rate in Indonesia from 1996-2022; (2) Changes in exchange rates affect changes in the current account balance in the short and long term; (3) The mechanism for changes in the current account deficit does not affect changes in the exchange rate